Monetary policy rules for Russia - Merkl, Christian; Vinhas de Souza, Lucio; Esanov, Akram (Journal of Comparative Economics, 2005)
The paper reviews the recent conduct of monetary policy and the central bank’s rule-based behavior in Russia. Using different policy rules, we test whether the central bank in Russia reacts to changes in inflation, output gap and the exchange rate in a consistent and predictable manner. Our results indicate that during the period of 1993-2002 the Bank of Russia has used monetary aggregates as a main policy instrument in conducting monetary policy.
Keywords: Monetary policy rules; exchange rate; central bank; Russia